Penggunaan Platform E-Commerce untuk Promosi dan Penjualan Produk Kerajinan di Kecamatan Sijunjung dengan OpenCart - Kurniawan, Ilham; Annas, Firdaus; Tigana, Adra (Yayasan Lembaga Studi Makwa, 2024)
The purpose of this writing is to design a promotional system for handicraft products using the OpenCart CMS, aimed at facilitating promotions. The main issue faced by handicraft products is the uncertainty regarding orders and sales. Even though the products produced meet consumer expectations, there are often situations where items already manufactured remain unsold or are not collected by the buyers who ordered them. Some of the most sought-after products, such as phone cases, Islamic gowns, men's shirts, and songket fabrics, face various challenges, including different payment methods and production issues such as broken threads or patterns that do not align with customer preferences. Payments are usually made in cash or via bank transfer, and products are typically collected directly by buyers. For out-of-town buyers, delivery is sometimes arranged using intercity buses. Currently, there are many technologies available to enhance product sales and notify customers that their orders are ready. This study adopts the Research and Development (R&D) method with a development model comprising planning, production, and evaluation stages. The result of this research is a web-based promotional media platform utilizing the OpenCart application, which has been validated as both valid and practical. The findings demonstrate that OpenCart can serve as an effective supporting medium to enhance the competitiveness of handicraft products in the Sijunjung district..